New bulk p-type skutterudites DD0.7Fe2.7Co1.3Sb12−xXx (X = Ge, Sn) reaching ZT > 1.3. (1st June 2015) - Rogl, G.; Grytsiv, A.; Heinrich, P.; Bauer, E.; Kumar, P.; Peranio, N.; Eibl, O.; Horky, J.; Zehetbauer, M.; Rogl, P.
Graphical abstract: Abstract: The best p-type skutterudites so far are didymium filled, Fe/Co substituted, Sb-based skutterudites. Substitution at the Sb-sites influences the electronic structure, deforms the Sb4 -rings, enhances the scattering of phonons on electrons and impurities and in this way reduces the lattice thermal conductivity. In this paper we study structural and transport properties of p-type skutterudites with the nominal composition DD0.7 Fe2.7 Co1.3 Sb11.7 {Ge/Sn}0.3, which were prepared by a rather fast reaction–annealing–melting technique. The Ge-doped sample showed impurities, which did not anneal out completely and even with ZT > 1 the result was not satisfying. However, the single-phase Sn-doped sample, DD0.7 Fe2.7 Co1.3 Sb11.8 Sn0.2, showed a lower thermal and lattice thermal conductivity than the undoped skutterudite leading to a higher ZT = 1.3, hitherto the highest ZT for a p-type skutterudite. Annealing at 570 K for 3 days proved the stability of the microstructure. After severe plastic deformation (SPD), due to additionally introduced defects, an enhancement of the electrical resistivity was compensated by a significantly lower thermal conductivity and the net effect led to a record high figure of merit: ZT = 1.45 at 850 K for DD0.7 Fe2.7 Co1.3 Sb11.8 Sn0.2 .